CeαMn1-αO2 catalysts supported over γ-Al2O3 prepared by modified redox-coprecipitation methods for n-hexane combustion - Quispe J.R. (2020)
A series of CeαMn1-αO2 catalysts supported on g-alumina with various molar concentrations of Ce (α, from 0 to 0.90) was synthesized by coprecipitation, applying two different precipitating agents, namely, sodium hydroxide (method 1) and sodium carbonate (method 2), with the use of sodium permanganate as a redox agent for precipitation. XRD profiles of the supported samples revealed the predominant abundance of a typical fluorite crystalline structure. TPR thermograms of supported samples were displaced towards lower temperatures with increasing Mn concentration, in contrast with the bulk samples. The supported Ce-Mn samples exhibited a greater performance in n-hexane elimination than did the corresponding simple oxides. The sample Ce0.33Mn0.67O2 obtained by method 2 presented the best activity, probably due to the enrichment of Ce4+, Mn3+ and Mn4+ surface species, an excess of superficial oxygen species and an easy reducibility as well as the lowest apparent activation energy.